Theory of Change Workbook: A Step-by-Step Process for Developing or Strengthening Theories of Change - Salib, Monalisa (USAID, 2022)
While over time theories of change have become synonymous with simple if/then statements, a strong theory of change should actually be a much more detailed, context-specific articulation of how we *theorize* change will happen under a program.

CLA Maturity Tool - Card Deck (Implementing Partners version 1) - USAID LEARN (USAID, 2022)
USAID’s Bureau for Policy, Planning and Learning (PPL) and its support mechanism, LEARN, have developed a Collaborating, Learning, and Adapting (CLA) Framework and Maturity tool to help USAID missions think more deliberately about how to plan for and implement CLA approaches that fit the mission’s context and assist them in achieving their development objectives. While the tool is intended primarily for USAID audiences to be used in participatory self-assessment workshops, the CLA Framework and maturity spectrum are relevant to a wider audience. USAID’s CLA Framework identifies key components and subcomponents of daily work that may be opportunities for intentional, systematic, and resourced CLA. The framework recognizes the diversity of what CLA can look like in various organizations and programs while also giving CLA structure, clarity, and coherence across two key dimensions: • CLA in the Program Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; and • Enabling Conditions: how an organization’s culture, business processes, and resource allocation support CLA integration. Recognizing that CLA is not binary—it’s not an issue of “doing it or not doing it”—PPL and LEARN have developed a spectrum of practice for each of the 16 subcomponents in the framework. The spectrum offers examples of what integration might look like at different stages: Not Yet Present, Emergent, Expanding, Advanced and Institutionalized. The maturity stage descriptions are only illustrative and are intended to spark reflection on current practice and opportunities for improvements. In this resource, each CLA subcomponent page describes the key concepts for that topic and includes a description of the maturity stages. Although the descriptions were originally developed for USAID, the majority of the concepts easily transfer or have equivalents in the partner community. For example, although organizations outside of USAID may not hold “Portfolio Reviews” (part of the Pause & Reflect subcomponent), the majority hold some type of meeting to review programmatic progress. This is the seventh version of the CLA Framework and maturity spectrum. PPL and LEARN will continue reviewed and periodically update them based on user feedback, so if you have comments about the content, please email learning@usaid.gov. We would also love to hear how you’ve used this content with your team or organization.

Collaborating, Learning and Adapting (CLA) Maturity Spectrum (v7) - USAID LEARN (USAID, 2022)
USAID’s Bureau for Policy, Planning and Learning (PPL) and its support mechanism, LEARN, have developed a Collaborating, Learning, and Adapting (CLA) Framework and Maturity tool to help USAID missions think more deliberately about how to plan for and implement CLA approaches that fit the mission’s context and assist them in achieving their development objectives. While the tool is intended primarily for USAID audiences to be used in participatory self-assessment workshops, the CLA Framework and maturity spectrum are relevant to a wider audience. USAID’s CLA Framework identifies key components and subcomponents of daily work that may be opportunities for intentional, systematic, and resourced CLA. The framework recognizes the diversity of what CLA can look like in various organizations and programs while also giving CLA structure, clarity, and coherence across two key dimensions: • CLA in the Program Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; and • Enabling Conditions: how an organization’s culture, business processes, and resource allocation support CLA integration. Recognizing that CLA is not binary—it’s not an issue of “doing it or not doing it”—PPL and LEARN have developed a spectrum of practice for each of the 16 subcomponents in the framework. The spectrum offers examples of what integration might look like at different stages: Not Yet Present, Emergent, Expanding, Advanced and Institutionalized. The maturity stage descriptions are only illustrative and are intended to spark reflection on current practice and opportunities for improvements. In this resource, each CLA subcomponent page describes the key concepts for that topic and includes a description of the maturity stages. Although the descriptions were originally developed for USAID, the majority of the concepts easily transfer or have equivalents in the partner community. For example, although organizations outside of USAID may not hold “Portfolio Reviews” (part of the Pause & Reflect subcomponent), the majority hold some type of meeting to review programmatic progress. This is the seventh version of the CLA Framework and maturity spectrum. PPL and LEARN will continue reviewed and periodically update them based on user feedback, so if you have comments about the content, please email learning@usaid.gov. We would also love to hear how you’ve used this content with your team or organization.

Collaborating, Learning, and Adapting Framework & Key Concepts (Implementing Partner Version 1) - USAID LEARN (USAID, 2022)
Although collaborating, learning, and adapting (CLA) are not new to USAID and its implementing partners, they often do not happen regularly or systematically and are not intentionally resourced. The CLA Framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: - CLA in the Program Cycle: how CLA is incorporated into planning and design processes throughout the Program Cycle in order to improve their effectiveness; and - Enabling Conditions: how an organization’s culture, daily operating processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.